Moscas ectoparasitas (Diptera, Hippoboscoidea) de morcegos (Mammalia, Chiroptera) do Estado do Paraná. II. Streblidae: chave pictórica para gêneros e espécies - Graciolli,Gustavo (2001)
A survey of batflies (Diptera, Streblidae) was done in Paraná State, Brazil during 1998 and 1999. Twenty-tree species in 10 genera were recorded. Two species of streblid batflies, Paraeuctenodes longipes Pessôa & Guimarães, 1936 and Metelasmus pseudopterus Coquillett, 1907, that have not been found in Paraná State were included, because they have been recorded in Rio Grande do Sul and São Paulo States. One species is new a record for Brazil: Trichobius jubatus Wenzel, 1976. In addition, twenty more species are new records for Paraná State: Trichobius joblingi Wenzel, 1966; T. tiptoni Wenzel, 1976; T. furmani Wenzel, 1966; T. longipes (Rudow, 1871); Paratrichobius longicrus (Ribeiro, 1907); Megistopada aranea (Coquillett, 1899); M. proxima (Séguy, 1926); Aspidoptera falcata Wenzel, 1976; A. phyllostomatis (Perty, 1833); Exastinion clovisi (Pessôa & Guimarães, 1936); Noctiliostrebla aitkeni Wenzel, 1966; Paradyschiria fusca Speiser; 1900; P. parvula Falcoz, 1931; Strebla chrotopteri Wenzel, 1976; S. diaemi Wenzel, 1966; S. guajiro (Garcia & Casal, 1965); S. mirabilis (Waterhouse, 1879), Paraeuctenodes similis Wenzel, 1976; Anastrebla caudiferae Wenzel, 1976; A. modestini Wenzel, 1966. The occurence of Paralrichabius longicrus on Pygoderma bilabiatum (Wagner, 1843), and Trichobius dugesioides dugesioides and Strebla mirabilis on Mimon bennettii (Gray, 1838) is reported for first time. Pictorial keys to species are presented and the gonopods of streblid batflies are illustrated.